Literary impostors : Canadian autofiction of the early twentieth century - Heidenreich, Rosmarin Elfriede, 1943- (McGill-Queen's University Press, 2018)
The first study to offer an in-depth, systematic examination of literary imposture in Canada viewed through the lens of autofiction.